Reduced inorganic sulfur in sediments of the mariculture region of Sanggou Bay, China - X Kang (Inter-Research, 2016)
Reduced inorganic sulfur (RIS) and organic matter (OM) in a mariculture region (Sanggou Bay, China; SGB) and at a reference station without mariculture were determined to assess the influence of mariculture on sulfide accumulation and the benthic environment. To this end, sediment acid-volatile sulfide (AVS), pyrite sulfur (pyrite-S), elemental sulfur (ES), OM, porosity, reactive iron, and pore water sulfate were measured. The results indicate that the concentration of RIS was negatively correlated with dissolved oxygen concentration. Principal component analysis showed that sulfide distribution was influenced by sediment porosity, OM, and reactive iron concentration. In addition, sulfide distribution was influenced by water current and water depth. More sulfide content accumulated at an oyster monoculture site than at a scallop/kelp polyculture site and a kelp monoculture site. We found no significant difference in ES concentration among the 3 mariculture types. While no significant influence on benthic OM accumulation was observed, except slightly enhanced reactivity of the OM (making it easily decomposable), mariculture activities in SGB significantly promoted sulfide accumulation compared to the reference station. However, there was no potential threat of toxic sulfide to the benthic biomass in SGB.